ANALYSIS OF ORGANIC AND MINERAL COMPONENTS IN CHIMNEY SOOT - TKACHUK, HANNA; TKACHUK, ANDRII; STREMETSKYI, OLEKSANDR (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The intensified use of solid biofuels, particularly wood, for residential heating has led to a significant increase in emissions of fine particulate matter and potentially hazardous substances, notably from domestic chimney combustion. This study addresses a critical environmental and public health issue by conducting a detailed chemical analysis of soot, which was collected from a residential chimney and presented predominantly as a dense, glossy, sticky resin – a hazardous form known as creosote. The primary objective was to establish the comprehensive elemental and organic chemical composition of this soot matrix to determine its potential toxicity and definitively identify the combustion source markers, particularly seeking evidence of uncontrolled domestic waste burning.Two complementary analytical techniques were employed. X-ray Fluorescence Spectroscopy (XRF) was utilized for the qualitative and quantitative determination of the mineral and elemental composition, focusing on both light and heavy elements, including potentially toxic metals (PTMs). The XRF analysis revealed a mineral fraction primarily composed of potassium (46.764 %) and calcium (42.180 %), which are strong markers for the combustion of biomass (wood). However, the analysis also demonstrated the non-trivial presence of PTMs. Specifically, zinc (0.837 %) and lead (0.102 %) were detected. While zinc is associated with painted wood, both metals are common components of printing inks, certain plastics, and galvanized materials. Their combined presence strongly supports the hypothesis that municipal solid waste was co-incinerated with wood fuel. An elevated sulfur content (5.074 %) further reinforced this, suggesting the burning of plastics, rubber, or paper, in the absence of coal or peat usage.For the organic profile, the soot extract was analyzed by Gas Chromatography-Mass Spectrometry (GC-MS). The experiment was conducted under two different temperature programs and flow split ratios (Regime 1: high split, high starting temperature; Regime 2: low split, low starting temperature) to ensure a comprehensive capture of both less volatile and highly volatile compounds. Regime 1, designed to analyze the structural backbone of the creosote, confirmed the source as wood pyrolysis by the massive dominance of levoglucosan, which is a major, stable thermal marker of cellulose pyrolysis. High concentrations of lignin-derived compounds were also found, including syringyl and guaiacyl derivatives, which are precursors to the condensed, resinous creosote fraction.
Keywords: soot; creosote; polycyclic aromatic hydrocarbons; X-ray fluorescence spectroscopy; gas chromatography-mass spectrometry